2016
DOI: 10.1080/13543776.2016.1203903
|View full text |Cite
|
Sign up to set email alerts
|

Polymers, scaffolds and bioactive molecules with therapeutic properties in osteochondral pathologies: what’s new?

Abstract: Promising tissue engineering based procedures have emerged as a therapeutic option for the treatment of osteochondral lesions. The development of multilayer scaffolds and the controlled release of bioactive molecules to promote in situ regeneration of both cartilage and bone are some of the latest technologies that intended to improve on the available traditional treatments. To confirm the potential of these novel approaches, long-term evaluation is necessary with special focus on studying the biological and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Collagen fibers within the lower zone, align vertical to the bone, and the main cell category gathers itself in columns [36]. Approaching the calcified zone, more chondrocytes have a tendency to express several forms of collagen, and the production of ECM is increased [37]. Chondrocyte metabolism is affected by growth factors, electrical fields, matrix composition, mechanical loads, and hydrostatic pressures [38].…”
Section: Articular Cartilagementioning
confidence: 99%
“…Collagen fibers within the lower zone, align vertical to the bone, and the main cell category gathers itself in columns [36]. Approaching the calcified zone, more chondrocytes have a tendency to express several forms of collagen, and the production of ECM is increased [37]. Chondrocyte metabolism is affected by growth factors, electrical fields, matrix composition, mechanical loads, and hydrostatic pressures [38].…”
Section: Articular Cartilagementioning
confidence: 99%
“…Morphology of scaffold surface is an important factor. While porosity of scaffold material mimics the microstructure of cancellous bone or cartilage, the surface properties of biomaterials play a major role in cellular interactions, such as cell adhesion, infiltration and proliferation [23,24]. In present study, morphological analyses demonstrated that osteoblasts and chondrocytes adhere on the surface and moved within the pores of the bilayer scaffolds of loofah+PLLA+cellulose and loofah+PLLA+chitin.…”
Section: Discussionmentioning
confidence: 75%
“…Bioactive factors are crucial in treating osteochondral defects. Growth factors are among the most frequently used chondrogenic differentiation factors in cartilage regeneration, and their effectiveness in treating osteochondral defects has been extensively verified [ 75 ]. Furthermore, unique chondrogenic−inducing factors, such as small molecule drugs and peptides, have been shown to have a higher chondrogenic capability [ [76] , [77] , [78] ].…”
Section: Articular Cartilage Regeneration Under Abnormal Conditionsmentioning
confidence: 99%